ANALISIS PENYEBAB ANAK PUTUS SEKOLAH BAGI KELUARGA MISKIN (Studi Kasus Anak Usia Sekolah Pada Keluarga Miskin di Kampung Lio Kota Depok) - Ahmad Yaneri; Vivi Suviani; Vonika, Nike (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Dropout is a condition where students cannot complete their learning program before the time is over or students do not finish their study program. However, the number of dropout cases can result in the low education of a nation and will affect the Human Development Index (HDI) ranking or the human development index. This study aims to identify and explain what factors cause children to drop out of school. The factors that influence children dropping out of school according to Baharuddin (1982), Dalyono (2008) and Johnston and Rivera (in Beder, 1990) are: Internal factors consisting of: a). Intelligence; b). Motivation; c). Level of Awareness; d). Dislike School. And external factors consisting of economics, school factors, and socio-cultural (society). There were 9 informants in this study. Three children drop out of school, Three parents drop out of school, Two teachers, One principal. Data collection techniques used are observation, interviews and documentation studies. The results showed that of the four internal factors that caused children or students to drop out of school, the most dominant factor was the factor of not liking school because they felt ostracized by their friends, making them uncomfortable in the school environment. Meanwhile, of the three external factors related to the cause of children or students dropping out of school, the school factor. The results of the analysis of problems and needs need attention from the government, schools and parents in developing children's abilities through formal education.